2020
DOI: 10.4025/actascihumansoc.v42i1.50492
|View full text |Cite
|
Sign up to set email alerts
|

Violência sexual e namoro: experiência de vitimização e impactos nos relacionamentos de adolescentes

Abstract: Este estudo objetiva analisar as experiências de vitimização por abuso sexual, em namoros, e seus impactos em adolescentes escolares. Trata-se de um estudo qualitativo com 5 escolares do ensino médio que sofreram violência sexual nas relações amorosas. Os dados foram interpretados com base na análise de conteúdo de Bardin. As unidades foram agrupadas em eixos temáticos: experiência de vitimização, percepções sobre violência, impactos e estratégias de enfrentamento e superação da violência sofrida. Os dados mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…Similarly, cross-sectional studies conducted by Silverman et al (2001), Ackard et al (20022007) and Banyard et al (2008) found that being the victim of physical and sexual violence was related to suicidal thoughts and suicide attempts. Similarly, in their qualitative study, de Sousa-Costa et al (2020) found feelings of fear and guilt and suicidal behavior in adolescent victims of sexual violence. In the same sense, Exner-Cortens et al (2013) showed in their longitudinal study of physical and psychological violence that female adolescent victims in Canada had a two-and threefold greater incidence of depressive symptoms and suicidal ideation, respectively.…”
Section: Magdolmentioning
confidence: 89%
“…Similarly, cross-sectional studies conducted by Silverman et al (2001), Ackard et al (20022007) and Banyard et al (2008) found that being the victim of physical and sexual violence was related to suicidal thoughts and suicide attempts. Similarly, in their qualitative study, de Sousa-Costa et al (2020) found feelings of fear and guilt and suicidal behavior in adolescent victims of sexual violence. In the same sense, Exner-Cortens et al (2013) showed in their longitudinal study of physical and psychological violence that female adolescent victims in Canada had a two-and threefold greater incidence of depressive symptoms and suicidal ideation, respectively.…”
Section: Magdolmentioning
confidence: 89%